The Etiological Causes of Hematuria Cases in Our Clinic - Aydınoğlu, A. Hakan; Turgut, Mehmet; Doğan, Yaşar; Kılıç, Mehmet; Kurt, Abdullah; Aygün, A. Denizmen (Fırat University, 2003)
Aim: To investigate the primary hematuria-causing factors in our clinic and their importance in diagnose. Material and method: In the present study, hematuria cases admitted to our clinic between January 1995 and December 1999 were retrospectively evaluated. Entity and frequency of these hematuria cases in the patient population of our clinic were also investigated. Results: Fifty nine (53.2 %) of cases were male and 52 (46.8%) were female, and mean average age was 7.2 ± 3.4 (One month-16 years) year. Macroscopic hematuria was seen in only 29 patients (26.1 %). Acute poststreptococcal glomerulonephritis was determined to be most frequent cause of hematuria in 39 cases (35.1%). Nephrotic syndrome and urinary tract infection were second and third causes, respectively. Conclusion: In developing countries frequency of acute poststreptococcic glomerulonephrite the most common cause of hematuria in our serial, was diminished by decrease on streptococcal infections, maintain its importance in our region.

Amaç: Hematüri nedeni ile yatırılan hastalarda esas nedenlerin irdelenmesi. Gereç ve yöntem: Bu çalışmada Ocak 1995- Aralık 1999 tarihleri arasında beş yıl süresince yataklı servise yatırılarak izlenen hematürili vakalar retrospektif olarak incelendi. Bulgular: Vakaların 59'u (%53.2) erkek, 52'si (%46.8) kız ve ortalama yaşları 7.2 ± 3.4 (1 ay-16 yıl) yıl idi. Yalnızca 29'unda (%26.1) makroskopik hematüri gözlendi. Hematüri tipi 67 (%60.3) vakada glomeruler ve 44 (%39.7) vakada ise nonglomeruler olarak belirlendi. En sık hematüri nedeni olarak 39 (%35.1) vakada akut poststreptokoksik glomerulonefrit bulundu. Nefrotik sendrom ikinci ve idrar yolu enfeksiyonu üçüncü sırada yer aldı. Sonuç: Gelişmiş ülkelerde streptokok enfeksiyon sıklığının giderek azalması ile birlikte hematüri serilerinde en sık neden olarak gözlenen APSGN azalırken, ülkemizde halen önemini korumaktadır.
Kliniğimizde İzlediğimiz Hematürili Vakalar Işığında Hematüri Nedenlerinin İrdelenmesi